Strategies for Social and Emotional Skills in the Inclusive Education of Students with Disabilities (Docentes 2.0 Journal, 2024)
In the current educational panorama, the issue of educational and social inclusion has become an extremely important aspect because educating a child from his early years is a priority in society. This research analyzed the impact of inclusive education strategies on developing emotional and social skills in students with disabilities. The study presented a systematic review based on a humanistic paradigm as a methodology with a qualitative and descriptive approach. The results revealed that using inclusion strategies by the teacher is essential for students to interact assertively with their environment and in all areas of their lives. From the results obtained, it was concluded that inclusion strategies significantly impact the learning process of students with disabilities. These skills play a crucial role in interacting and relating effectively with others, leading to substantial improvements in achieving academic and personal goals. The interconnection between the strategies used and learning becomes evident, evidencing how developing social and emotional competencies can catalyze the educational progress of students with disabilities.
Keywords: Education; inclusion; paradigms; pedagogy